CEREBRAL SALT WASTING SYNDROME IN A PATIENT WITH PRIMARY CNS LYMPHOMA - Prochazka, Vit; Kubova, Zuzana; Raida, Ludek; Papajik, Tomas; Paucek, Boris; Indrak, Karel (Biomedical papers, 2009)
Background: In patients with severe central nervous system (CNS) diseases, life-threatening hyponatremia results from two main causes: the syndromes of inappropriate secretion of antidiuretic hormone (SIADH) and cerebral salt wasting (CSW). Clinical manifestations of the two conditions may be similar but their pathogeneses are fundamentally diverse. Distinguishing SIADH from CSW is based on the differential diagnoses of dilutional hyponatremia due to an excessive amount of water in the body (SIADH) and depletional hyponatremia caused by extensive natriuresis (CSW).Methods and Results: We report the case of a 48-year-old, previously healthy male with a diffuse large B-cell lymphoma affecting the area of the basal ganglia and the right part of the thalamus and oppressing the third brain ventricle. After admission to the Department of Hemato-oncology, the patient was soporous and laboratory tests revealed severe serum hyponatremia, hypochloremia, hypoosmolality and marked polyuria with normal serum levels of urea, creatinine, glucose and calcium. Urinalysis showed high specific gravity of the urine and extreme wasting of sodium, chloride and kalium ions. Overall fluid balance was negative. After the first chemotherapy cycle, the CT scan confirmed regression of the tumour site. This was accompanied by patient's improved cognition as well as decreased polyuria and urine electrolyte excretion. Eventually, it was concluded that the diagnosis was cerebral salt wasting syndrome.Conclusion: We noted a so far unpublished case of a 48-year-old male with the diagnosis of primary CNS lymphoma (DLBCL) affecting deep structures of the brain and associated with CSW.
Keywords: Cerebral salt wasting/Lymphoma/Hyponatremia